2023
DOI: 10.3390/ma16030914
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study of the Influence of Pre-Existing Impact Damage on the Low-Velocity Impact Response of CFRP Panels

Abstract: This paper presents an experimental and numerical investigation on the influence of pre-existing impact damage on the low-velocity impact response of Carbon Fiber Reinforced Polymer (CFRP). A continuum damage mechanics-based material model was developed by defining a user-defined material model in Abaqus/Explicit. The model employed the action plane strength of Puck for the damage initiation criterion together with a strain-based progressive damage model. Initial finite element simulations at the single-elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Different numerical approaches have been recently used to simulate the complex failure of composites under LVI loads [37][38][39][40][41][42]. While accurate results of interlaminar and intralaminar damage prediction were obtained [43,44], less attention has been paid to permanent indentation/deformation due to impact [45][46][47][48]. Measuring permanent indentation or dent depth, i.e., the distance between the surface of the laminate and the lowest point in the dent of an impact, is commonly used to inspect BVID in aeronautical structures [49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…Different numerical approaches have been recently used to simulate the complex failure of composites under LVI loads [37][38][39][40][41][42]. While accurate results of interlaminar and intralaminar damage prediction were obtained [43,44], less attention has been paid to permanent indentation/deformation due to impact [45][46][47][48]. Measuring permanent indentation or dent depth, i.e., the distance between the surface of the laminate and the lowest point in the dent of an impact, is commonly used to inspect BVID in aeronautical structures [49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…Xiang et al 22 conducted a continuous numerical analysis of two types of impacts with constant total energy on steel parking structure columns, and found that a single impact had a greater degree of damage to the column than two impacts. Rezasefat et al 23 conducted experimental and numerical studies on the low‐speed impact response of CFRP panels with pre‐existing impact damage. Sebaey et al 24 used impact as a damage initiator to study the effects of impact frequency, position, and energy on the crashworthiness of glass/epoxy composite tubes.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have applied physics-based simulations, machine learning (ML), and data-driven techniques to investigate the mechanical behaviour of defect-and porecontaining parts [44][45][46][47][48][49]. Owing to the outstanding capabilities of ML models, handling large and complex datasets obtained from XCT or simulations of parts with pores is now possible.…”
Section: Introductionmentioning
confidence: 99%